Ionic Dialysance and Determination of Kt/V in on-line Hemodiafiltration with Simultaneous Pre- and Post-dilution. Issue 5 (May 2013) - Créput, Caroline; Toledano, Daniel; Petitclerc, Thierry
Purpose: A direct determination of Kt/V using ionic dialysance for estimating K and bio-impedancemetry for estimating V is compared with the usual indirect estimation based on the second generation Daugirdas equation during a new technique of hemodiafiltration with simultaneous pre- and postdilution (mixed-HDF). Methods: In 31 informed consented patients, the urea distribution volume (V) is estimated by total body water (VBCM ) measured by the Body Composition Monitor (BCM; Fresenius Medical Care, Bad Homburg, Germany) based on bio-impedance spectroscopy. The value (KOCM t)/VBCM is calculated during 114 mixed-HDF sessions (duration 4 hours) from the measurement of ionic dialysance KOCM by the OCM module, standard on the 5008 dialysis monitor (Fresenius Medical Care, Germany). The single pool (Kt/V)sp is determined from blood urea concentration measurements using the Daugirdas equation. Results: Mixed-HDF is a very high-efficiency hemodialysis with a delivered dialysis dose Kt/V near from 2 per 4-hour session. (KOCM t)/VBCM (1.97 ± 0.28) is consistent with (Kt/V)sp (2.01 ± 0.34) with a correlation coefficient at 0.72. Conclusions: Direct calculation of Kt/V from estimating K by OCM and V by BCM is consistent with the usual indirect estimation by the second generation Daugirdas equation. Therefore, the regular determination of V by BCM allows the estimation of single-pool Kt/V at each session without the need of blood sampling.